GAMBARAN RESILIENSI PADA PENYINTAS PTSD (POST TRAUMATIC STRESS DISORDER) AKIBAT BULLYING - Zahra, Fatimatuz; Sholichah, Ima Fitri; Amelasasih, Prianggi (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2024)
Background: When individuals are faced with stressors or difficult situations,some of them are able to rise and recover, while others are trapped. Eachindividual has a different reaction when experiencing a traumatic event.Objective: This study aims to obtain an overview of resilience in PTSD (PostTraumatic Stress Disorder) survivors due to bullying. Method: The subject of thisstudy were 1 person, according to the criteria determined by the researcher. Datacollection techniques use interviews and observation. In this study, the stepstaken by researchers were qualitative data analysis according to Miles andHuberman's interactive model. In this study, the data validity test carried out wasa triangulation of methods and data sources. The description of resilience is seenfrom Reivich and Shatte's dimensions. Result: The results showed that theresearch subjects had good resilience. This is shown in the dimensions of thesubject, namely emotional regulation, impulse control, optimism, causal analysis,empathy, self-efficacy, and reaching out. Conclusion: This research hasimplications for the subjects to survive the difficult situations they face assurvivors of PTSD (Post Traumatic Stress Disorder) due to bullying.